2009
DOI: 10.1159/000232939
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Bicenter Study Investigating the Diagnostic Value of Procalcitonin in Patients with Acute Appendicitis

Abstract: Background: Procalcitonin (PCT) is an established laboratory marker for disease severity in patients with infection and sepsis. In addition, PCT has been shown to be an effective marker for a limited number of localized infections. However, whether or not PCT has any diagnostic value for acute appendicitis, still remains unclear. The purpose of this prospective bicenter study was, therefore, to determine whether or not the PCT levels in the serum of patients with acute appendicitis have any diagnostic value. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…Several diagnostic tests are used for appendicitis including leucocyte count, neutrophil percentage, C-reactive protein (CRP), D-Dimer, and Procalcitonin. [3][4][5][6] However, today, there is no single laboratory test or imaging modality for diagnosing acute appendicitis with 100% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic tests are used for appendicitis including leucocyte count, neutrophil percentage, C-reactive protein (CRP), D-Dimer, and Procalcitonin. [3][4][5][6] However, today, there is no single laboratory test or imaging modality for diagnosing acute appendicitis with 100% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have investigated the ability of PCT to diagnose localized infection. To the best of our knowledge, there are only five previous studies that addressed the role of PCT in diagnosing appendicitis, three of which investigated the pediatric population and two investigated the adult population [11,[22][23][24][25]. Kafetzis et al [23] found that PCT elevation greater than 0.5 ng/mL had a sensitivity of 73 % and a specificity of 92.3 % in identifying perforated appendicitis in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used tests are white blood cell count and serum C-reactive protein (CRP) levels. Erythrocyte sedimentation rate (ESR) serves as an indicator of inflammation and procalcitonin (PCT) levels have also been used recently (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic value of PCT in AA in adolescents or adults has rarely been studied (6). Over the course of an inflammatory process, bacterial invasion of the appendix wall is followed by release of bacterial endotoxins (22).…”
mentioning
confidence: 99%